Enhancing Dynamism and Innovation in Japan's Business Sector - Jones, Randall S.. (OECD Publishing, 2015)
Innovation is key to boosting economic growth in the face of a rapidly ageing population. While Japan spends heavily on education and R&D, appropriate framework conditions are essential to increase the return on such investments by strengthening competition, both domestic and international, and improving resource allocation. Upgrading corporate governance would encourage firms to maximise profits and invest their large cash reserves. To promote open innovation in a global framework, it is necessary to improve universities and expand their role in business R&D, while increasing international collaboration in R&D from its current low level. Venture capital-backed firms and start-ups should play a key role in commercialising innovation. To make venture investment a growth driver, it is important to expand the role of business angels and foster entrepreneurship. SMEs, which account for 70% of employment, should contribute more to innovation
Keywords: Environment; Economics; Japan